Caracterización de la velocidad y dirección del viento para evaluación del potencial energético en el campus matriz de la Universidad Técnica de Cotopaxi - Azogue Sulqui, Diego Fabricio (2022)
The present technological proposal consists of characterizing the wind speed and direction by means of the anemometer sensor DNA121, in order to know the energy potential at the Technical University of Cotopaxi in the Matriz Campus, since there is a lack of knowledge about the characterization of the wind energy potential existing in the area. Applying the field research, allowed obtaining the data on site, in which the instrument was programmed to measure every 10 minutes for 16 days to obtain the desired variables through the statistical characterization of the Excel software tool, the wind rose was obtained, This allows me to compare with NASA data as a referential system, concluding that in most days that coincides in 27% of the total data collected that the wind comes from the South at about 97.45 ° to the NE at about 63.37 ° with reference to the fourth quadrant considering the greatest energy potential at an average speed of 0. 4 m/s deducting that we have mostly stochastic variables.